Edukasi Seksual Kepada Orang Tua oleh Guru Pendidikan Anak Usia Dini sebagai Strategi Perlindungan Anak di Taman Kanak-Kanak Kristen Taman Firdaus Balige Sumatera Utara - Nimar Nimar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study is a descriptive qualitative study that aims to describe sexual education provided by parents at Taman Firdaus Christian Kindergarten, Balige, North Sumatra. Data were obtained through direct interviews with the Principal, teachers, and several parents. The results showed that teachers and parents at Taman Firdaus Christian Kindergarten had provided basic teaching about the physical differences between boys and girls. However, an explanation of the genitals and their names had not been given because it was considered inappropriate for the age of the children. The main focus of teaching was on norms of politeness and privacy, although a comprehensive understanding of sexuality had not been achieved. Understanding of boundaries and privacy was taught by emphasizing the importance of maintaining privacy, such as not showing genitals to the opposite sex and maintaining physical distance. However, there were challenges such as the limitations of school policies in separating boys' and girls' toilets. The use of appropriate language in sexual education has been carried out well, although consistency in the school environment and at home needs to be improved. Parental involvement in children's sexual education is considered important, but there are obstacles in the form of parental discomfort in discussing sexuality topics with their children at home. The descriptive approach in this qualitative study aims to describe in detail the events, phenomena, and social situations that are the focus of the study. Analysis is carried out by giving meaning, interpreting, and comparing the data obtained to gain a deep understanding of the subject being studied.